Exploring the clinical factors affecting lithium dose and plasma level and the effect of brand - Carol Paton; Paul Bassett; Olivia Rendora; Thomas R. E. Barnes (SAGE Publishing, 2024)
Background: Optimal use of lithium involves adjustment of the dose, to keep the plasma level within the narrow, recommended range. Brand-specific prescribing has long been considered critical to achieving this aim, but this is a convention based on very limited data. Objectives: To explore the effect of selected demographic and clinical factors on the relationship between lithium dose and plasma level and determine whether there is an independent effect of lithium brand. Design: Analysis of clinical audit data collected in 2023 as part of a quality improvement programme addressing the use of lithium, conducted by the Prescribing Observatory for Mental Health. Methods: Data were collected from clinical records using a bespoke proforma, submitted online and analysed using SPSS. Results: Data were submitted for 4405 patients who had been prescribed solid-dosage formulations of lithium for more than a year. Priadel ® was prescribed for 3722 (84%) of these patients, Camcolit ® for 112 (2.5%) and the prescription was written generically for 554 (12.5%). Compared with Priadel, where Camcolit was prescribed, the mean daily dose was 10% higher and the mean plasma lithium level was 11% higher. A multivariable analysis was conducted to explore the relationship between selected clinical variables and maintenance lithium dose. This found that in 4213 patients whose most recent plasma lithium level was between 0.3 and 1.19 mmol/L, the variables age, sex, ethnicity, psychiatric diagnosis and the severity of chronic kidney disease were independently associated with dose while the brand of lithium prescribed was not. Conclusion: Our findings replicate those of previous studies with respect to the demographic and clinical variables that can be expected to influence lithium dosage in routine clinical practice. This reinforces the need to titrate the dosage for each individual patient, to achieve and maintain the target plasma level. However, the findings suggest that the Priadel and Camcolit brands of lithium are essentially interchangeable.